Peripheral Artery Occlusive Disease Among Patients With Chronic Myeloid Leukemia Receiving Tyrosine Kinase Inhibitors: A Cross-Sectional Case-Control Study - Thanawat Rattanathammethee (2018)
© 2017, © The Author(s) 2017. Background: There were some reports of peripheral artery occlusive disease (PAOD) associated with nilotinib usage in chronic myeloid leukemia (CML). These complications in other tyrosine kinase inhibitors are revealed as unknown. Materials and methods: We determined the prevalence of PAOD in patients with CML as compared with matched-control population by cross-sectional case-control study. Peripheral artery occlusive disease was screened by ankle-brachial index (ABI). Results: In total, 78 CML and 156 matched-control patients were included. The median age was 55 years. In all, 61 (78.2%) were on imatinib and 13 (16.7%) were on nilotinib, whereas 4 patients (5.2%) were on dasatinib. Prevalence of low ABI ( < 0.9) was 9.0%, and nilotinib users had the highest prevalence of low ABI of 30.7%. All cases with low ABI were not shown to be clinically overt of PAOD. There were well-balanced characteristics between cases of CML and matched control except in higher levels of hypercholesterolemia in the control. Interestingly, CML had more amounts of pathologic ABI than the control (odds ratio: 2.09, 95% confidence interval: 0.71-6.21), and diagnosis of diabetes found it to be independent of the risk of PAOD. Conclusions: Peripheral artery occlusive disease was higher among pa tients with CML than the control, especially in patients who had diabetes.